"Here, There and Everywhere": The Beatles, America, and Cultural Globalization, 1964–1968. (11th January 2016) - LEBOVIC, SAM
Abstract : This article explores the Beatles' invasion of America as a moment of cultural globalization. Paying attention to the political economy underpinning the Beatles' success, the international hybridity at the heart of their cultural work, and the diverse ways in which Americans interpreted the Beatles, the article argues that the band was a primary vector of pop culture's increasing globality in the 1960s. More broadly, the article argues that the Beatles' trajectory reveals that cultural globalization cannot be understood as a process either of homogenization or of creolization. Rather, the Beatles represented an increasingly unified and commodified culture that simultaneously served to reproduce cultural differences when different social formations projected their own meanings onto the hybridized group. The article therefore provides new perspectives on the historical significance of the iconic band and on the intersections between global and domestic cultural history in the 1960s, as well as suggesting a new framework for thinking about both the history and the contradictions of cultural globalization.